2013
DOI: 10.1155/2013/168916
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Green Synthetic Protocol for Novel Trimetallic Nanoparticles

Abstract: Metallic nanocomposites and nanotubes can be rapidly prepared under microwave irradiation (MW) from an aqueous solution of metallic precursors in the presence of trisodium citrate as a reductant. For the nanotubes nanoparticles are stabilized by poly(Nvinyl-2-pyrrolidone) (PVP), a protecting agent. PVP is a typical capping and structure-directing agent used for the synthesis of various metallic nanostructures. In this work, we have demonstrated for the first time an MW irradiation approach for the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Metallic nanoparticles have been considered as an important area of research due to their unique and tunable physicochemical properties and biological activities as compared to their bulk counterparts. In recent years, a numerous techniques such as physical vapour deposition, chemical vapour deposition, sol-gel synthesis, microwave assisted synthesis, ultrasonication, electrochemical synthesis, precipitation method, and biosynthesis have been reported for the synthesis of metallic nanoparticles [1][2][3][4][5][6][7][8][9][10][11]. Biosynthesis of metallic nanoparticles by using biological organisms and plant extract is an ecofriendly alternative to those involving toxic and hazardous chemicals [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanoparticles have been considered as an important area of research due to their unique and tunable physicochemical properties and biological activities as compared to their bulk counterparts. In recent years, a numerous techniques such as physical vapour deposition, chemical vapour deposition, sol-gel synthesis, microwave assisted synthesis, ultrasonication, electrochemical synthesis, precipitation method, and biosynthesis have been reported for the synthesis of metallic nanoparticles [1][2][3][4][5][6][7][8][9][10][11]. Biosynthesis of metallic nanoparticles by using biological organisms and plant extract is an ecofriendly alternative to those involving toxic and hazardous chemicals [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the MW irradiation method facilitated the fabrication of trimetallic nanocomposites and nanotubes. As a result, high-resolution scanning electron microscopy (HRSEM) images indicated that these particles were close to nanocomposite (Ag-Pt) and nanowire (Au) structures (length = 792 nm and width = about 99 and 51 nm) [ 90 ]. Additionally, HRSEM images of the fabricated Au-Pd-Pt trimetallic NPs revealed them to be of uniform nanotube shapes, length, and width of the nanotube being ~141 nm and 152 nm, respectively [ 90 ].…”
Section: Greener and Sustainable Synthesis Of Trimetallic Npsmentioning
confidence: 99%
“…As a result, high-resolution scanning electron microscopy (HRSEM) images indicated that these particles were close to nanocomposite (Ag-Pt) and nanowire (Au) structures (length = 792 nm and width = about 99 and 51 nm) [ 90 ]. Additionally, HRSEM images of the fabricated Au-Pd-Pt trimetallic NPs revealed them to be of uniform nanotube shapes, length, and width of the nanotube being ~141 nm and 152 nm, respectively [ 90 ]. In another study, the authors reported on eco-friendly production of a Au/Pt/Ag trimetallic nanocomposite (~20–51.3 nm) by trisodium citrate-assisted reduction of ions under MW heating conditions [ 91 ]; the fabricated nanocomposites comprised gold nanowires and silver/platinum bimetallic NPs.…”
Section: Greener and Sustainable Synthesis Of Trimetallic Npsmentioning
confidence: 99%
“…appeared at 2 = 38.98 ∘ , 45.19 ∘ , 66.07 ∘ , and 76.67 ∘ ascribed to Ag (1 1 1), Pd (2 0 0), Ag (3 1 1), and Ag (2 0 0) planes, respectively. The sizes of BNCs were calculated by using Scherrer's equation [26,28,29] and were found to be ∼ 6 nm in size. Table 1 shows the calculated size of crystalline nanoparticles and the identified crystal planes.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Nanoparticles' interaction with L-cysteine was reported [20][21][22][23] as sensing of L-cysteine. Among the wide range of structural variations offered by BNPs, the core-shell structure is an important one, in which one element goes to the inner core and another forms an outer shell [24][25][26][27][28][29][30] and the functionalization depends on the shell of the core-shell BNPs. By considering the above facts, Ag/Pd core-shell nanocomposites have been synthesized and characterized; sensing and Raman scattering applications have been presented here.…”
Section: Introductionmentioning
confidence: 99%